PENCABUTAN PENGADUAN PADA KASUS TINDAK PIDANA KEKERASAN DALAM RUMAH TANGGA BERDASARKAN PASAL 75 KITAB UNDANG-UNDANGHUKUM PIDANA DIKAITKAN DENGAN KEADILAN RESTORATIVE JUSTICE (STUDI KASUS KEPOLISIAN SEKTOR TAMPAN PEKANBARU) - Iis Fatmala Sari; Mexsasai Indra; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Domestic violence is not a new thing, but it is a crime that has long been rooted in the culture of society. As set forth in Article 51 to Article 53 of Law Number 23 Year 2004 on the Elimination of Domestic Violence is a complaint offense, in which the victim can determine whether the case has been reported to be terminated and revoked by his complaint or will continue until before the demand is read out at Court. In some cases of domestic violence that often ends in the settlement of cases Domestic Violence ends a verdict for the imposition of a prison sentence to the perpetrator.Based on the background of the problems that the authors describe above, the authors are interested to conduct research with the title: "Removal of Complaints in Cases of Criminal Acts of Domestic Violence Under Article 75 Criminal Law Code Related to Justice Restorative Justice (Case Study Police Sector Tampan Pekanbaru)" . With the formulation of the problem that is how the process of settlement of Criminal Violence in Households based on restorative justice by Pekan Sector Police Tampan Pekanbaru? And what are the obstacles to solving domestic violence based on justice of restorative justice by Pekanbaru Charming Sector Police?This research is a type of sociological legal research (empirical), which is the research of sociological law is as an effort to see the effect of the validity of positive law on the life of the community, because in this study the authors directly conduct research on the location or place studied in order to provide a complete picture and clear about the problem under study. From this study the authors obtained the result that the process of revocation of the complaint must be approved by the victim which is done through the mediation process suggested by the Tampan Police. Barriers often experienced by the Tampan Police is because most victims and victims do not want to reconcile with the perpetrator because they still feel resentment or disappointed with the act of the perpetrator.Key Words : Domestic Violence, Restorative Justice, Police Sector of Tampan, Complainment